Od "Nesimo jih vun!" k zamolku ulice - Zavratnik, Simona (Družboslovne razprave, 2016)
In the article, the case of the uprising movement in Slovenia (2012-2013) is used to examine the processes and triggers of the emergence, culmination and ending of protest cycles, whereby special emphasis is placed on their local-global specifics and the strategies of delegitimisation of protests and passivation of masses of angry people. The analysis is based on interviews and focus groups with representatives of the majority of the uprising groups in Slovenia. The research findings show that the uprisings in Slovenia represent a watershed moment in the transition to an increasingly pronounced control state as reflected in the criminalisation of the protests and the wider context of everyday life, sliding towards a police state and modified regulations for "organising" protests.
Keywords: Družbena gibanja; Social movements; Protesti; Protests; Represija; Repression; Slovenia; Slovenija; society; družba; vstajniška gibanja